Consciousness = 0: The Inexistence of Consciousness - Hamidi, Nabil (My University, 2025)
This article advances a universal empirical and ontological principle: every centerless system known to science is material, while every immaterial system known to thought requires an off-center. Across cosmology, physics, chemistry, biology, ecology, network science, and thermodynamics, all centerless phenomena—such as spacetime, the cosmic microwave background, electromagnetic fields, quantum wavefunctions, gases, plasmas, delocalized orbitals, neural nets, ecosystems, and internet architectures—are fully physical systems that are centerless (Dodelson & Schmidt, 2020; Griffiths, 2017; Kundu et al., 2015; Campbell et al., 2020; Newman, 2018). No immaterial centerless phenomenon exists in mathematics, logic, semantics, or phenomenology. Neuroscience demonstrates that consciousness has no anatomical, functional, or structural center (Crick & Koch, 2003; Dehaene, 2014), and because centerless systems must be material—yet consciousness possesses no physical properties—it cannot exist materially or immaterially. Consciousness therefore has no ontological status : Consciousness = 0.